Essays in Technology Management and Policy : Selected Papers of David J. Teece. - Leung, T. P.; Qin, H. S. (World Scientific, 2003)
Over the last 50 years or so, a number of textbooks, monographs and even popular books have been published on nonlinear control theory and design methods. In the area of classical control, for example, there exist books concerned with phase-plane analysis, describing function approach, absolute stability and so on. In the area of modern control there are those related to optimal control, using differential geometry and the differential algebra method, variable structural control, H-infinite control and so on. These books have been useful in promoting the development of automatic control science and technology. Since 1990 there have been many new results and contributions in the area of nonlinear control. This book introduces those topics to interested readers. It should also benefit automation engineers, researchers and scholars in related fields.